Erythrocyte radiolabelling: in vitro comparison of chromium, technetium, and indium in undamaged and heat damaged cells. Issue 7 (July 1986) - Peters, A M; Osman, S; Reavy, H J; Chambers, B; Deenmamode, M; Lewis, S M
Abstract : The stability of the commonly used red cell radio labels chromium-51, indium-(111 or 113m), and technetium-99m, within intact red cells and stroma and their distribution within the cell were compared in undamaged and heat damaged red cells in relation to the clinical use of heat damaged cells in the assessment of splenic function. Chromium-51 labelled haemoglobin both in undamaged and heat damaged cells; indium predominantly labelled haemoglobin in undamaged cells but labelled stroma in heat damaged cells, even when the cells were labelled before heating; technetium-99m predominantly labelled haemoglobin in undamaged cells but only labelled stroma in heat damaged cells if these were heated before labelling. Indium was more firmly bound by stroma prepared from heat damaged cells, and technetium-99m showed a high rate of elution both from cells and stroma, although this rate was lower for heat damaged cells.